Lead and Zinc Groundwater Contaminant Transport Modelling Using MT3DMS in Xaysomboun Province, Lao PDR - Siharath, Phoummixay; Vilaychaleun, Somchay; Thammathevo, Khampasith; Sonemanivong, Chankhachone; Kannitha, Soulyphan; Phommakone, Bounmy; Keokhamphui, Keoduangchai; Tabios, Guillermo III Quesada (Darul Yasin Al Sys, 2023)
Contaminant transport modelling is commonly applied in the Groundwater Modelling System (GMS). Modular Three-Dimensional Multispecies Transport (MT3DMS) package is one of other packages, developed by the U.S. Geological Survey, this research presents the employing of the M3TDMS package as excellent tools to establish the 3D conceptual model of contaminant transport modeling, simulate and predict the multispecies of Lead and zinc substances which transport in the groundwater, there are 15 boreholes that were observed and monitored, the results of the contaminant transport modeling was found the Lead(Pb) contaminant transport with initial concentrations of 3.96 mg/l at borehole MB48 as point source, the concentration reduced to 0.1 mg/l, after 3,650 days simulation. The initial zinc (Zn) concentration of 0.886 mg/l at borehole CV04 decreases to 0.023 mg/l after 3,650 days simulation.